2007
DOI: 10.1159/000098885
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Management and Postnatal Separation of Omphalopagus and Craniopagus Conjoined Twins

Abstract: Two cases of prenatally diagnosed conjoined twins are presented: a set of omphalopagus twins sharing a common liver, and a set of craniopagus with involvement limited to the skull. In both cases, prenatal diagnosis allowed accurate planning of pre- and postnatal management. Prenatal management involved serial imaging and counseling with participation of different specialists according to imaging findings. In the rare case of conjoined twins, an interdisciplinary approach is required, with feto-maternal special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…The chance of successful postnatal separation of conjoined twins depends on the complexity of vital organ fusion 1 . For omphalopagus twins, the degree of fusion of the hepatobiliary and gastrointestinal systems is not easy to determine prenatally and can pose a significant surgical challenge 2 .…”
Section: Letters To the Editor Three-dimensional Power Doppler In Thementioning
confidence: 99%
“…The chance of successful postnatal separation of conjoined twins depends on the complexity of vital organ fusion 1 . For omphalopagus twins, the degree of fusion of the hepatobiliary and gastrointestinal systems is not easy to determine prenatally and can pose a significant surgical challenge 2 .…”
Section: Letters To the Editor Three-dimensional Power Doppler In Thementioning
confidence: 99%
“…18 In our experience, planned postnatal surgical separation led to favorable outcomes in two cases, a case of omphalopagus and a case of craniopagus conjoined twins (Figs 9 to 12). 55 In the case of omphalopagus twins, cardiac anomalies were detected prenatally in only one of the twins, but there were no signs of shared cardiac structures, making continuation of pregnancy to a viable stage reasonable, since successful postnatal surgical separation was possible. In the case of craniopagus twins, the absence of prenatal sonographic signs of shared neural tissue showed that postnatal surgical separation might be successful as well.…”
Section: Planning Perinatal and Postnatal Managementmentioning
confidence: 99%
“…In the case of craniopagus twins, the absence of prenatal sonographic signs of shared neural tissue showed that postnatal surgical separation might be successful as well. 55 Detailed prenatal counseling of parents is crucial in decisionmaking with regard to continuation of pregnancy and planning postnatal management. An interdisciplinary medical team, involving obstetricians, neonatologists, pediatric surgeons and anesthetists, should undertake counseling.…”
Section: Planning Perinatal and Postnatal Managementmentioning
confidence: 99%
See 2 more Smart Citations